Editorial and Introduction. (June 2019) - Wills, David
Abstract : Welcome to the summer issue of Legal Information Management (LIM) which celebrates the fiftieth anniversary of the British and Irish Association of Law Librarians (BIALL). Back in 1999, on Friday 16th April 1999 to be precise, a BIALL Council meeting took place that was held at the Institute of Advanced Legal Studies in London. The minutes of that meeting record that, Before the meeting opened, Mary Blake [then President of BIALL] informed those present that the date was a special one in BIALL history, as it was 30 years to the day that BIALL was established. She had marked the occasion by bringing a birthday cake and Michael Maher [then Chair of the Association] provided bottles of Champagne for a toast after lunch.